2003
DOI: 10.1073/pnas.1531901100
|View full text |Cite
|
Sign up to set email alerts
|

Angiopoietin-related growth factor (AGF) promotes epidermal proliferation, remodeling, and regeneration

Abstract: We report here the identification of an angiopoietin-related growth factor (AGF). To examine the biological function of AGF in vivo, we created transgenic mice expressing AGF in epidermal keratinocytes (K14-AGF). K14-AGF mice exhibited swollen and reddish ears, nose and eyelids. Histological analyses of K14-AGF mice revealed significantly thickened epidermis and a marked increase in proliferating epidermal cells as well as vascular cells in the skin compared with nontransgenic controls. In addition, we found r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
105
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 114 publications
(107 citation statements)
references
References 34 publications
(33 reference statements)
1
105
1
Order By: Relevance
“…Recently, we (8)(9)(10) and others (11)(12)(13)(14)(15) identified several genes encoding proteins containing both the coiled-coil domain and the fibrinogen-like domain. Although these factors were initially predicted to function as ligands for Tie receptors, they bound neither Tie1 nor Tie2.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, we (8)(9)(10) and others (11)(12)(13)(14)(15) identified several genes encoding proteins containing both the coiled-coil domain and the fibrinogen-like domain. Although these factors were initially predicted to function as ligands for Tie receptors, they bound neither Tie1 nor Tie2.…”
mentioning
confidence: 99%
“…Therefore, they are currently orphan ligands and designated angiopoietin-like proteins (Angptls) or angiopoietin-related proteins (ARPs). Several studies show that Angptl͞ARP family proteins possess potent activities in the vascular system (8)(9)(10)(11)(12)(13)(14)(15)(16). Angptl1 and Angptl2 have been reported to possess weak endothelial cell-sprouting activities (11,12); however, there is little information as to their physiological functions.…”
mentioning
confidence: 99%
“…Furthermore, statistically significant positive correlation was found between AGF and systolic blood pressure or mean arterial pressure in patients with preeclampsia. The overall effect of AGF is associated with angiogenesis and act as pro-angiogenic factors [10]; in addition, AGF can promote epidermal proliferation, remodeling and regeneration [11]. AGF can also affect glucose, lipid and energy metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Its most interesting member (in terms of glucose, lipid homeostasis and insulin sensitivity) is ANGPTL6 (also called 'angiopoietin-related growth factor' [AGF]). ANGPTL6 was first identified in 2003, and has been characterized as an angiogenic factor involved in epidermal proliferation and wound healing [9,13]. Recently, it was shown that ANGPTL6 is involved in the development of obesity and its related insulin resistance in mouse models [14].…”
Section: Introductionmentioning
confidence: 99%
“…The mechanisms by which it stimulates energy expenditure and insulin sensitivity, and the nature of the tissues targeted by the protein have yet to be established. In mice, Angptl6 is expressed predominantly in the liver, but also in haematopoietic cells [13]. In humans, the ANGPTL6 gene is located on chromosome 19p13.2, but nothing is known of its expression and function.…”
Section: Introductionmentioning
confidence: 99%